1992
DOI: 10.1002/1097-0142(19920215)69:4<930::aid-cncr2820690416>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathologic study on neural invasion in cancer of the pancreatic head

Abstract: Thirty‐four patients who had resection of cancer of the pancreatic head were examined clinicopathologically to elucidate neural invasion of cancer of the pancreatic head to the extrapancreatic nerve plexus. Invasion of cancer to the retropancreatic tissue (rp+) was observed in 29 (85%) of the 34 patients, and neural invasion to the extrapancreatic nerve plexus was observed in 21 (72%) of the 29 patients with rp+. The incidence of invasion to the second region of the nerve plexus of the pancreatic head was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 8 publications
2
47
2
Order By: Relevance
“…Several detailed pathohistologic studies (Nagakawa et al, 1992a;Nakao et al, 1996) have shown that PNI is one of the causes of locoregional recurrence in resected pancreatic cancer. But the prognostic value of PNI is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several detailed pathohistologic studies (Nagakawa et al, 1992a;Nakao et al, 1996) have shown that PNI is one of the causes of locoregional recurrence in resected pancreatic cancer. But the prognostic value of PNI is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreatic carcinoma, nerve invasion is the major pathway in the retroperitoneal direction [24]. In rectal carcinoma, neural invasion has a strong relationship with local recurrence of the tumor [25].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of carcinoma invasion into the extratumoral nerve plexus was studied in pancreatic cancer [18,19]. Nakao et al [19] reported that intrapancreatic neural invasion was observed in 116 of 120 (90%), of which 80 (69%) showed extrapancreatic nerve involvement.…”
Section: Discussionmentioning
confidence: 99%